Maternal Imagery in Bible Translation: A Comparative Analysis of Divine Nurturing Metaphors Across Indigenous Languages in Ghana - Grace Sintim Adasi; Sanatu Fusheini (Journal of Mother-Tongue Biblical Hermeneutics and Theology)
This study examines how maternal imagery in the Bible is translated and interpreted in divine metaphors of Ghanaian Languages – Twi, Ewe, and Dagbani. It analyses the translations of maternal nurturing metaphors in these three indigenous languages through a comparative analysis of key Bible passages (Isa. 66:13, Hos. 11:3-4, and Deut. 32:18), exploring their theological and cultural implications. This study uses a methodology that combines textual analyses with ethnolinguistic methods to compare the semantic range and cultural resonance of maternal imagery traits, as salient in translation discourses. The study reveals important variances in how maternal metaphors are preserved, modified, or recreated in these languages, revealing degrees of interrelatedness among linguistic constraints and worldviews regarding divine nurturing. The study contributes to the growing body of literature on the subject of Bible translation in indigenous African languages and gender-inclusive language in sacred texts.